2017
DOI: 10.21042/amns.2017.1.00012
|View full text |Cite
|
Sign up to set email alerts
|

Video Observation of Perseids meteor shower 2016 from Egypt

Abstract: The results of single television observations of Perseid meteor shower in 2016 are presented. The Perseid shower occurs from 17 July to 24 August, peaking on or around August 12 every year. In 2016, the peak of the Perseids was Night of Aug 11 to the morning of Aug 12. The meteor video observations in Egypt are carried out at The National Researcher Institute of Astronomy and Geophysics (NRIAG). The system consists of TV - cameras Watec -902H Ultimate with the lens DV10x8SA-1 (8-80 mm (10x)) capable of recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
(2 reference statements)
0
6
0
Order By: Relevance
“…Squalene is the active ingredient antibacterial anti-inflammatory and has the effect on hypertension hepatocirrhosis, diabetes, brochitis and other diseases. Dl-.alpha.-Tocopherol can eliminate the deposition of lipofuscin in cells, improve normal function of cells, slow down the senescence process of cells, promote the synthesis of protein renewal and so on [32][33][34][35]. Ribitol is an important intermediate in the synthesis of antihepatitis drug Silybin.…”
Section: Analysis Of Gc-msmentioning
confidence: 99%
“…Squalene is the active ingredient antibacterial anti-inflammatory and has the effect on hypertension hepatocirrhosis, diabetes, brochitis and other diseases. Dl-.alpha.-Tocopherol can eliminate the deposition of lipofuscin in cells, improve normal function of cells, slow down the senescence process of cells, promote the synthesis of protein renewal and so on [32][33][34][35]. Ribitol is an important intermediate in the synthesis of antihepatitis drug Silybin.…”
Section: Analysis Of Gc-msmentioning
confidence: 99%
“…The information received by the first relay routing node was X 1 , the information received by the malicious eavesdropping node was Z 1 , and the information received by the receiving node was Y 1 . According to the existing theories, the capacity of safe channel is: When VANET adopted the regional cooperation mode, the source node cooperated with the surrounding nodes to complete the information joint sending and the selection of relay routers [19,20]. The destination node cooperated with the surrounding nodes to complete the information receiving.…”
Section: Architecture Designmentioning
confidence: 99%
“…Various modern instruments make more in-depth the chemical research of T.S. Taking it as the main research object, andthe extraction from three different organic solvents was detected and identified by FT-IR and GC-MS [22][23][24]. The results showed that extract contained a large number of bioactive components, and most components are healthy and abundant [25].…”
Section: Instructionsmentioning
confidence: 99%